FOREIGN DIRECT INVESTMENT AND THE MATCHING CONCEPT: DEVELOPING MODEL ON DOWNSTREAM EFFECT - Takele, Yitbarek; Adeniyi-kie, Adewale (European Scientific Journal, ESJ, 2013)
The attractiveness of FDIs to a particular location are reflections of perceived benefits which will aid the FDI and the Host community ability to achieve their various objectives which can be captured by examining the characteristics exhibited by the many stakeholders contributing to economic development of the location and also the goals of the investment. Studies of FDIs and Host countries at microeconomic levels reveal the intricate interactions between the sectors. More importantly, the downstream study of the elements making up the country reveals the structure of the FDIs and Investments and the interactions between the varying factors across the whole country though such studies are lacking in the extant literature. This paper attempted to develop a model at the downstream level which can capture FDI and investment situation using the matching concept which have not been done so far.